2020
DOI: 10.1038/s41419-020-2333-3
|View full text |Cite
|
Sign up to set email alerts
|

UHRF1-repressed 5’-hydroxymethylcytosine is essential for the male meiotic prophase I

Abstract: 5'-hydroxymethylcytosine (5hmC), an important 5'-cytosine modification, is altered highly in order in male meiotic prophase. However, the regulatory mechanism of this dynamic change and the function of 5hmC in meiosis remain largely unknown. Using a knockout mouse model, we showed that UHRF1 regulated male meiosis. UHRF1 deficiency led to failure of meiosis and male infertility. Mechanistically, the deficiency of UHRF1 altered significantly the meiotic gene profile of spermatocytes. Uhrf1 knockout induced an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 82 publications
0
9
0
Order By: Relevance
“…Ubiquitin-like PHD and RING finger domain-containing protein 1 (UHRF1), also known as nuclear protein 95 (Np95) in mice or inverted CCAAT box-binding protein of 90 kDa (ICBP90) in humans, is a unique epigenetic effector important for multiple aspects of epigenetic regulation, including the recognition and maintenance of various histone modifications ( 15 , 16 ). Early studies show the canonical function of UHRF1 as a multifunctional protein is in the recruitment of DNA methyltransferase 1 (DNMT1) to DNA loci, thereby facilitating DNA hypermethylation ( 15 , 17 ), which plays important roles in cell proliferation, cell cycle progression, and tumor aggressiveness ( 16 , 18 , 19 ). In addition, the structural basis shows UHRF1 acts as a transcriptional repressor through its binding to unmodified Arg-2 and trimethylated Lys-9 of histone H3 by the PHD and TTD domains, respectively ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ubiquitin-like PHD and RING finger domain-containing protein 1 (UHRF1), also known as nuclear protein 95 (Np95) in mice or inverted CCAAT box-binding protein of 90 kDa (ICBP90) in humans, is a unique epigenetic effector important for multiple aspects of epigenetic regulation, including the recognition and maintenance of various histone modifications ( 15 , 16 ). Early studies show the canonical function of UHRF1 as a multifunctional protein is in the recruitment of DNA methyltransferase 1 (DNMT1) to DNA loci, thereby facilitating DNA hypermethylation ( 15 , 17 ), which plays important roles in cell proliferation, cell cycle progression, and tumor aggressiveness ( 16 , 18 , 19 ). In addition, the structural basis shows UHRF1 acts as a transcriptional repressor through its binding to unmodified Arg-2 and trimethylated Lys-9 of histone H3 by the PHD and TTD domains, respectively ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that the conditional knockout of UHRF1 in the testis leads to complete infertility in males 42,43 . In addition, UHRF1 gene polymorphisms are closely associated with oligospermia in Chinese men 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the conditional knockout of UHRF1 in the testis leads to complete infertility in males. 42,43 In addition, UHRF1 gene polymorphisms are closely associated with oligospermia in Chinese men. 44 Although the process of oogenesis was not affected, a large proportion of the embryos derived from the Uhrf1knockout (KO) oocytes died before reaching the blastocyst stage, which might have been caused by a maternal effect.…”
Section: Myd88/nf-κb Signaling Pathway Promoted the Pro-inflammatory ...mentioning
confidence: 99%
“…However, only the tip of the iceberg regarding the regulatory mechanisms and functions of RNA-binding factors as key determinants of SSC homeostasis has been explored. UHRF1 (also known as NP95 or ICBP90) is best known for its function in epigenetic regulation in multiple biological processes, including male germ cell meiosis and early embryo development (Cao et al, 2019;Chen et al, 2013;Dong et al, 2019;Muto et al, 2002Muto et al, , 2006Newkirk and An, 2020;Pan et al, 2020;Takada et al, 2021;Tien et al, 2011;Wu et al, 2020). It has a powerful effect on the regulation of DNA-related epigenetic modifications, but its role in RNA metabolism is largely unexplored.…”
Section: Introductionmentioning
confidence: 99%